2017
DOI: 10.13189/ujar.2017.050210
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Salt Water Intrusion on Maize (Zea mays) and Rice (Oryza sativa) Production under Climate Change Scenarios in Bagamoyo District-Tanzania

Abstract: Salt water intrusion is a challenge on production of human staple foods Zea mays and Oryza sativa in the changing climate, along the global coastal zones. Information on how salinity affects these crops is essential in developing scientific mitigations for sustainable food production. This study was conducted to investigate salt water intrusion and its impacts on Zea mays and Oryza sativa production in Bagamoyo District, Tanzania. Soil and water samples were collected along 14 km of Wami River for determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…data showed that the southwestern and eastern parts are experiencing high precipitation decreases and temperature increases. In addition to affirming perceived droughts in the region, other studies have documented the alarming effects of climate change, including saltwater intrusion into estuaries and freshwater aquifers(Ligate et al, 2017), which has greatly affected the production of major crops such as rice and maize. The spatially explicit information on climate variables, trends, and patterns presented in this work provides an in-depth reference to guide communities in developing appropriate measures for adapting to the effects of climate change.…”
mentioning
confidence: 99%
“…data showed that the southwestern and eastern parts are experiencing high precipitation decreases and temperature increases. In addition to affirming perceived droughts in the region, other studies have documented the alarming effects of climate change, including saltwater intrusion into estuaries and freshwater aquifers(Ligate et al, 2017), which has greatly affected the production of major crops such as rice and maize. The spatially explicit information on climate variables, trends, and patterns presented in this work provides an in-depth reference to guide communities in developing appropriate measures for adapting to the effects of climate change.…”
mentioning
confidence: 99%